Implementation of a prospective study for enhancing surveillance of invasive bacterial infections in North Africa. (February 2022) - Smaoui, Hanen; Tali-Maamar, Hassiba; Zouhair, Saïd; Bouheraoua, Selma; Mefteh, Khaoula; Bouskraoui, Mohammed; Amiche, Amine; Khris, Mouloud; Deghmane, Ala-Eddine; Taha, Muhamed-Kheir
Highlights: Real time PCR is increasingly used for the diagnosis of invasive bacterial infections Real time PCR was implemented in three North African countries for surveillance Quality assurance schemes were also implemented The results suggest the predominance of Neisseria meningitidis group B ABSTRACT: Objectives: We implemented a project named MENINGSTOP in three countries of North Africa (Algeria, Morocco and Tunisia). The main objective was to use real-time PCR to detect, identify and type the three main agents ( Neisseria meningitidis, Streptococcus pneumoniae and Haemophilus influenzae ) responsible for invasive bacterial infections (IBI). Methods: The protocol of WHO and US CDC for real-time PCR was used to detect and type the three bacterial agents in clinical samples. We also designated two quality exercises using an external interlaboratory study and cross-testing of 10% of randomly selected samples. Results: Among the 752 samples tested, 18% were positive for one of the three agents. N. meningitidis was the most frequent globally reaching 9% of all samples (7% to 17% range) followed by S. pneumoniae 8% of all samples (6% to 15%). Group B meningococci was the most frequent (74% of all positive samples for meningococci and ranging from 50% to 90%). Quality assurance showed >85% correlation scores. Conclusions: Real-time PCR can help improving epidemiological surveillance. Data confirm the prevalence of meningococci B. Our project adds a reliable tool to enhance surveillance and to help decision making in vaccination strategies against IBI.